The impossible relation with the 'other' in 'The Time of Friendship' - Gomes, Fernando (2014)
This paper aims to demonstrate that of all Bowles’s short stories, “The Time of Friendship” probably most subtly represents the complexity of human relations and the essence of the author’s perception of the confrontation between the West and its alterity: the presumptive attempt to assimilate the “other’s” culture and the impossibility of a genuine relation between peoples where cultures diverge fundamentally. The paper also intends to show that this short story summarises the favorite themes of the author, particularly the criticism of both the colonialists and the separatists in their annihilation of a geopolitical ideal, as well as his nostalgia for colonial and pre-colonial times; a perspective that indicates an orientalist bias.